Legal Analysis of the Supervision on Hygiene and Sanitation Application Aspects of Restaurant - Shalmont, Jerry; Yap, Abigail Angeline; Maharani, Aurelia Gisa; Khuin, Khuin; Putri, Rafirstka Madyah; Nevada, Valonia (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
A restaurant is a type of business that focuses on food services, equipped with facilities and equipment to carry out the processes of food or beverage preparation, storage, serving, and selling to the public at its premises. In managing a restaurant, the implementation of hygiene sanitation becomes a very important aspect, as it is an effort to control risk factors that could lead to contamination of the food being handled. Improper application of hygiene and sanitation can result in occurrences that are detrimental to consumers. This study applies a normative research methodology that is founded on constructive legal standards and their practical use in the real world situations. The findings of this investigation discuss one of the restaurants in Indonesia, which is known not to implement the proper hygiene and sanitation standards for restaurants, as well as the legal consequences and responsibilities of the hygiene for the losses experienced by its consumers.